2004
DOI: 10.1677/jme.0.0320279
|View full text |Cite
|
Sign up to set email alerts
|

Human immature germ cells and ejaculated spermatozoa contain aromatase and oestrogen receptors

Abstract: It is now well established that oestrogens play a part in germ cell function. These hormones are synthesised by the cytochrome P450 aromatase (P450 arom) and act via two kinds of receptor (ER and ER ). Although the presence of aromatase and oestrogen receptors in mammalian testis is now well documented, the localisation of these proteins in human germ cells is not yet clear. The primary purpose of the current study was to look for the expression of aromatase and oestrogen receptors in human germ cells. Human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
93
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(104 citation statements)
references
References 75 publications
10
93
0
1
Order By: Relevance
“…This sperm separation technique could effectively acquire sperm populations with high motility and normal morphology free of seminal plasma, debris, microbial contamination, and residual cells (immature germ cells or polynuclear cells). This was confirmed by our microscopy inspection and has been shown in previous reports [16,17,19,21,22]. Sperm motility was monitored Fig.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This sperm separation technique could effectively acquire sperm populations with high motility and normal morphology free of seminal plasma, debris, microbial contamination, and residual cells (immature germ cells or polynuclear cells). This was confirmed by our microscopy inspection and has been shown in previous reports [16,17,19,21,22]. Sperm motility was monitored Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Routine semen analysis monitored by a computer-assisted semen analyzer (IVOS; Hamilton-Thorne, Beverly, MA, U.S.) revealed that spermatozoa were within the normal range stipulated by WHO1999 guidelines. To separate high motile and morphologically normal spermatozoa from semen, the liquefied ejaculate was washed on a two-layer (90 % and 45 %) discontinuous Percoll (GE Healthcare; Piscataway, NJ, U.S.) gradient, a modified protocol described previously [16,17,19]. After centrifugation at 400 g for 18 min, the cell pellets from the 90 % layer were washed twice in Earle's balanced salts (Sigma; St. Louis, MO, U.S.).…”
Section: Semen Preparationmentioning
confidence: 99%
“…For removing the round cells (immature germ cells and leukocytes) and debris, and collecting high motile and low motile spermatozoa respectively from normal and asthenozoospermic semen, the liquefied semen samples were washed in a discontinuous Percoll (GE Healthcare, USA) gradient consisting of four successive layers (90%, 76%, 57% and 45%), which was a modification of the protocol described previously [24][25][26]. After centrifugation at 300 g for 20 min at room temperature, high motile spermatozoa in donors' semen and low motile spermatozoa in patients' semen were separated respectively from the 90% layer and from the interface 76%-57%.…”
Section: Sample Preparationmentioning
confidence: 99%
“…In order to confirm the separated sperm fractions free from round cells, the c-kit (as the marker of immature germ cells) and CD45 (as the marker of leukocytes) were amplified from cDNA samples as previously reported [25,26]. GAPDH was amplified as an internal control.…”
Section: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
See 1 more Smart Citation